EFFECTOF VARIABILITYCURVE NUMBER ON PEAK OF HYDROGRAPHFOR AL-KHOSER RIVER CATCHMENT - سمير يونس سحر (Journal of Engineering and Sustainable Development, 2017)
Water is an important natural resource, the research to develop ways of use and maintain this source is continuous. Rainfall and runoff are of sources of surface water. It is difficult to get the runoff hydrograph due to the effects of watershed characteristics, antecedent moisture content of the soil, and storm properties. Many ways were developed to estimate the runoff hydrograph such as the Soil Conservation Services method, which depends on curve number. The TR -55 model was calibrated toobtain the best results based on the measured data of a number of storms of the Al- Khoser seasonal river in Nineveh province in the Republic of Iraq. The model performance was evaluated based on the statistical parameters to compare the measured values with predicted for both runoff volume and peak of flow values. The TR-55 model was applied within the reasonable range of the curve number and for different depths of rainfall to evaluate their effect on the runoff volume and peak flow. All considered statistical parameters to evaluate the sensitivity curve number on peak flow and runoff volume that the most important factor is the rain depth, the depths between (10-25) mm be great sensitivity and vice versa. Also, for all considered rainfall depth, the increase of curve number over the actual values shows more sensitivity than values of less than actual one.